Case Report: The price of intraoperative cell salvage? - implantation metastases of meningioma in both lungs and left cubital fossa - He, Mengyao; Yu, Shengping; Luo, Wenjun; Zhang, Yu; Liu, Wenchao; Sun, Cuiyun; Huang, Qiang (Frontiers in Oncology, 2025)
Meningiomas are common Central Nervous System (CNS) tumors, typically benign, but they can occasionally metastasize or exhibit aggressive behavior. We present a case of meningioma with metastasis to unique sites (pulmonary and left cubital fossa) and intracranial recurrent progression. This case highlights challenges in managing recurrent and metastatic meningioma and the potential risks of intraoperative cell salvage (IOCS).